1962
DOI: 10.1002/j.1551-8833.1962.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Available Chlorine Residuals for Small Nonpublic Water Supplies

Abstract: For many years, municipal water treatment facilities have been producing potable water using coliform organisms as an index of water disinfection. In individual water supplies, where constant supervision is unavailable and where the physical and biological character of the raw water fluctuates rapidly, a more stringent standard of disinfection is needed. Superchlorination is recommended to provide a factor of safety for these fluctuations and to reduce the necessary chlorine contact time. This study recommends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Few vegetative cells were recoverable after incubation in 1000 mg l -1 (1.25%) and 5000 mg l -1 (6.25%) household bleach, and viable C. difficile cells were reduced to below the limit of detection (<10 CFU ml -1 ) in 8000 mg l -1 (10%) household bleach ( Figure 5A ). As pH alters the ratio of hypochlorite (HOCl) to the hypochlorite ion (OCl - ), and thus, the effectiveness of bleach (Baumann and Ludwig, 1962), these data suggested that the pH of the aqueous solution may alter the effectiveness of sodium hypochlorite. To test this hypothesis, vegetative cells grown to an OD 600 of 1.0 in BHIS medium were pelleted and suspended in pre-reduced 1X PBS (pH 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…Few vegetative cells were recoverable after incubation in 1000 mg l -1 (1.25%) and 5000 mg l -1 (6.25%) household bleach, and viable C. difficile cells were reduced to below the limit of detection (<10 CFU ml -1 ) in 8000 mg l -1 (10%) household bleach ( Figure 5A ). As pH alters the ratio of hypochlorite (HOCl) to the hypochlorite ion (OCl - ), and thus, the effectiveness of bleach (Baumann and Ludwig, 1962), these data suggested that the pH of the aqueous solution may alter the effectiveness of sodium hypochlorite. To test this hypothesis, vegetative cells grown to an OD 600 of 1.0 in BHIS medium were pelleted and suspended in pre-reduced 1X PBS (pH 7.4).…”
Section: Resultsmentioning
confidence: 99%
“…The idea behind the Ct concept is that for a given disinfectant, the product Ct is approximately constant for a given level of inactivation (Baumann and Ludwig 1962). The original use of this incorporated the idea of the dilution coefficient and a time exponent; this has its basis in the Chick–Watson law of disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiology has so often been seen as a purely descriptive science, and this belies the voluminous work done in mathematical biology applied to the food, home and personal care, and pharmaceutical industries. The`Ct' concept, obtained from disinfection rates, is used to set disinfection times against, for example, Giardia cysts (Baumann and Ludwig 1962;Wickramanayake et al 1985;Finch et al 1993). The rationale behind the canning process is based on thermal disinfection modelling, albeit it on a less than precise model (Anderson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Treating the water sample with 40 ppm chlorine for 3 to 5 min resulted in only .2-to .3-log reduction of bacterial population. In contrast, a 2-log kill of most common bacteria, such as Escherichia coli, in drinking water at 2 to 5 C and pH 8.5, requires less than .5 ppm for 5 min (Baumann and Ludwig, 1962). The low disinfecting action of chlorine in chiller water apparently resulted from competing reactions of chlorine with dissolved organic and inorganic matters, which reduced the availability of chlorine to act against microorganisms.…”
Section: Disinfectionmentioning
confidence: 89%